2005
DOI: 10.1111/j.1547-5069.2005.00059.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk Perception and Compliance With Quarantine During the SARS Outbreak

Abstract: This research indicates the need for greater credibility in public health communications to increase compliance with quarantine protocols and to contain outbreaks of new and deadly infectious diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
224
0
10

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(249 citation statements)
references
References 25 publications
15
224
0
10
Order By: Relevance
“…Unlike several other studies of resistance to scientific evidence, [30][31][32] corrective information from the CDC Web site successfully corrected misperceptions about MMR causing autism. However, the correction also reduced vaccination intent among parents with the least favorable vaccine attitudes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike several other studies of resistance to scientific evidence, [30][31][32] corrective information from the CDC Web site successfully corrected misperceptions about MMR causing autism. However, the correction also reduced vaccination intent among parents with the least favorable vaccine attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…22 Resistance to scientific evidence about health risks is also a serious concern. [30][31][32] It is therefore important to determine whether corrective information about MMR and other vaccines provokes a similar response. We hypothesize that respondents with the least favorable vaccine attitudes will increase their belief in false claims and decrease their intent to vaccinate in response to corrective information.…”
Section: Resultsmentioning
confidence: 99%
“…However, research in Singapore during SARS found that only 4% of respondents in a representative population sample had worn a face mask in the preceding three days 7. SARS-related research from Toronto, Canada focused on compulsory quarantine and voluntary quarantine/isolation, mostly in health care workers rather than in the general population 8,9. Compliance with compulsory quarantine was reported as high 9.…”
Section: Introductionmentioning
confidence: 99%
“…The literature, including recent studies of the H1N1 response, has demonstrated a relationship between concern (risk perception) and behavioural change, including responses to infectious disease threats (Leung et al, 2003; Cava et al, 2005; Abbate et al, 2006; Brewer et al, 2007; Jones and Salathe, 2009; Rubin et al, 2009; Eastwood et al, 2010; Manuell and Cukor, 2011). The study’s results did not reflect such a strong association.…”
Section: Discussionmentioning
confidence: 99%